2021
DOI: 10.1093/jamiaopen/ooab021
|View full text |Cite
|
Sign up to set email alerts
|

Information needs and perceptions of chatbots for hypertension medication self-management: a mixed methods study

Abstract: Objective Chatbots have potential to deliver interactive self-management interventions but have rarely been studied in the context of hypertension or medication adherence. The objective of this study was to better understand patient information needs and perceptions of chatbots to support hypertension medication self-management. Materials and Methods Mixed methods were used to assess self-management needs and preferences for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Age, IT skills, preference for talking to computers, perceived utility, positive attitude, and perceived trustworthiness were found to be associated with AI acceptability [25,26]. Australia and New Zealand [35] 4 (15) Canada [27,[36][37][38] 6 (23) China [22,32,33,39,40] 1 (4) France [41] 2 (8) India [24,42] 1 (4) Korea [48] 1 (4) Saudi Arabia [29] 1 (4) Switzerland [30] 5 (19) United Kingdom [23,26,31,43,44] 1 (4) United Kingdom, Cyprus, Australia, the Netherlands, Sweden, Spain, United States, and Canada [28] 3 (12) United States [25,45,46] Type of publication 24 (92) Journal papers [22][23][24][25][26][27][28][29][31][32][33][34][35][36][37]…”
Section: Stage 5: Collating Summarizing and Reporting Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Age, IT skills, preference for talking to computers, perceived utility, positive attitude, and perceived trustworthiness were found to be associated with AI acceptability [25,26]. Australia and New Zealand [35] 4 (15) Canada [27,[36][37][38] 6 (23) China [22,32,33,39,40] 1 (4) France [41] 2 (8) India [24,42] 1 (4) Korea [48] 1 (4) Saudi Arabia [29] 1 (4) Switzerland [30] 5 (19) United Kingdom [23,26,31,43,44] 1 (4) United Kingdom, Cyprus, Australia, the Netherlands, Sweden, Spain, United States, and Canada [28] 3 (12) United States [25,45,46] Type of publication 24 (92) Journal papers [22][23][24][25][26][27][28][29][31][32][33][34][35][36][37]…”
Section: Stage 5: Collating Summarizing and Reporting Resultsmentioning
confidence: 96%
“…All the studies showed at least moderate acceptability, or >50% of the participants showed acceptance toward the use of AI in health care, albeit only for minor conditions [ 26 ]. Age, IT skills, preference for talking to computers, perceived utility, positive attitude, and perceived trustworthiness were found to be associated with AI acceptability [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations